Academic librarianship - Evans, G. Edward, 1937-; Greenwell, Stacey (ALA Neal-Schuman, 2018)
This updated edition enables readers to understand how academic libraries deliver information, offer services, and provide learning spaces in new ways to better meet the needs of today's students, faculty, and other communities of academic library users.